Altered hippocampal fast oscillations and GABAergic circuits in neuregulin 1 over-expressing mice - Nissen, W (2012)
Neuregulin 1 (NRG1) is a growth factor implicated in neurodevelopment and postnatal maintenance of synaptic circuits. Its gene has been associated with schizophrenia, and the expression of the type I isoform (NRG1tyI) is increased in patients’ brains. Earlier behavioural phenotyping of mice over-expressing NRG1tyI revealed impairment in hippocampus-dependent spatial working memory. This present work investigates the effects of increased NRG1tyI expression on hippocampal network functioning in these mice. Fast network oscillations, specifically at gamma frequencies, were studied in CA3 hippocampal slices in a carbachol model using cellular and extracellular microelectrode recording techniques. The peak frequency of field potential oscillations was significantly reduced in slices from NRG1tyI mice compared to wild-type littermates. In addition, NRG1tyI mouse slices were more prone to develop epileptiform activity. During rhythmic activity, the balance of phasic excitation and inhibition was significantly altered in principal cells of NRG1tyI mice. Inhibitory synaptic input was more sustained, while excitatory synaptic currents were kinetically unchanged but larger and more variable in amplitude. Together, these data suggest altered functioning of the GABAergic inhibitory circuits that generate and maintain gamma oscillations. Because parvalbumin-expressing (PV+) interneurons are a major target of NRG1 signalling, the inhibition from PV+ interneurons to pyramidal cells was examined next. Channelrhodopsin-2-mediated photostimulation of PV+ cell axons failed to show changes in GABAergic inhibition of CA3 pyramidal cells in NRG1tyI mice. However, synaptic miniature glutamatergic neurotransmission was reduced in identified PV+ basket cells (BCs) and axo-axonic cells (AACs) but not in pyramidal cells. The change was expressed postsynaptically, affecting NMDA receptor- but not AMPA receptor-mediated currents. The data suggest that NRG1tyI over-expression results in alterations in PV+ interneuron types, particularly at the glutamatergic synapses that excite these cells. These changes and the altered gamma oscillations are already evident in late adolescence — before the age at which cognitive deficits are detectable.